Was Blumer a cognitivist? Assessing an ethnomethodological critique. (30th March 2018) - Hammersley, Martyn
Abstract: A major target of criticism for ethnomethodology has been cognitivism. In its broadest sense this term refers to any account of human behaviour that treats psychological features of agents – including beliefs, attitudes, and interpretations – as factors explaining their behaviour. While much criticism of cognitivism has been directed at neuroscientists and philosophical materialists, the range of targets has been wider than this, even including sociologists such as Herbert Blumer and symbolic interactionists. In this article I outline this criticism of Blumer and assess it. My conclusion is that, despite some misreading, his work does fall into the broad category of cognitivism. However, I question the grounds for the ethnomethodological critique.